Vector properties of the O(1D2) fragment produced from the photolysis of ozone in the wavelength range of 298 to 320 nm. - Horrocks, S; Pearson, P; Ritchie, G (2006)
The speed averaged translational anisotropy and electronic angular momentum polarization of the O(1D2) atomic fragment formed from the photodissociation of ozone in the atmospherically important long wavelength region of the Hartley band (298 to 320 nm) have been measured using resonance enhanced multiphoton ionization time of flight mass spectrometry. The translational anisotropy parameter, beta, is found to decline from 1.1 for photolysis at 300 nm to a minimum value of 0 at 310 nm which is the threshold for production of O(1D2) in conjunction with the O2(a 1Deltag v = 0) molecular cofragment. For photolysis wavelengths greater than 310 nm, O(1D2) is formed from the dissociation of internally excited ozone molecules. The corresponding beta parameters are markedly lower than for atomic fragments produced with the same speed from the photolysis of ground state ozone molecules. This result is consistent with two different pathways contributing to the photolysis of internally excited ozone at the longest wavelengths studied corresponding to initial internal excitation either in the symmetric or asymmetric stretching vibration. In addition, the polarization of the atomic angular momentum has been determined with the incoherent polarization parameters a0(2)(||) and a0(2)(_|) increasing from values of -0.53 and -0.62 at 300 nm to -0.37 and -0.19 at 317 nm, consistent with the increasing contribution from the photolysis of internally excited ozone as the dissociation wavelength lengthens. Evaluation of these alignment parameters allows the populations of the magnetic substrates, mj, to be determined. For example, for a photolysis wavelength of 303 nm the populations of mj = 0, +/- 1, +/- 2 are in the ratio of 0.36: 0.56: 0.08 and this ratio is essentially independent of the photolysis wavelength. The coherent contribution to the atomic polarization is quantified by the Re{a1(2)(||, _|)} and Im{a1(1)(||, _|)} parameters and these are found to vary from -0.21 and 0.21 at 300 nm to -0.04 and 0.24 at 313 nm, respectively.